Effects of the Minimum Wage on Infant Health - George Wehby; Dhaval M. Dave; Robert Kaestner (Institute for the Study of Labor (IZA), 2016)
The minimum wage has increased in multiple states over the past three decades. Research has focused on effects on labor supply, but very little is known about how the minimum wage affects health, including children's health. We address this knowledge gap and provide an investigation focused on examining the impact of the effective state minimum wage rate on infant health. Using data on the entire universe of births in the US over 25 years, we find that an increase in the minimum wage is associated with an increase in birth weight driven by increased gestational length and fetal growth rate. The effect size is meaningful and plausible. We also find evidence of an increase in prenatal care use and a decline in smoking during pregnancy, which are some channels through which minimum wage can affect infant health. Labor market policies that enhance wages can thus affect wellbeing in broader ways, and such health effects should enter into any cost-benefit calculus of such policies.
Keywords: I1; I3; J2; J3; 330; minimum wage; health; infant; prenatal care; smoking; income; pregnant women